Movement index and history of injuries as a predictor of injuries in Icelandic elite soccer players - Jóhanna Ingadóttir 1982- (2013)
Pre-season screening is getting more popular among athletes in competitive sport to identify athletes that may be at risk of sustaining injuries. The aim of this study was to perform a pre-season movement screening, vertical jump height measurement, balance test (hop lunge) and single leg pistol squat (pistol squat) as well as record injuries during a season for male and female elite soccer players from Iceland (n = 41). History of former injuries were also gathered for each player. The movement screening consisted of overhead squat (OHS), single leg squat (SLS) and side squat. The purpose was to use the tests to predict injuries sustained during season. Players that got injured during season had significantly lower total index of SLS/OHS/side squat for left side (yes: 177.7, no: 198.5, p = 0.032), total index of SLS/OHS/side squat (yes: 175.3, no: 197.0, p = 0.027) and knee angle for dominant leg (yes: 67.0°, no: 77.0°, p = 0.0005) and non-dominant leg (yes: 59.0°, no: 78.3°, p = 0.002) in pistol squat, compared to players that did not get injured during the season. Players that had history of former hip/back injuries were at higher risk of sustaining injury during season (OR = 7.61, p = 0.006). A different injury profile was observed between injured and non-injured group (injuries sustained during season) when male and female players were analysed seperately. In a multivariate analysis, difference between dominant and non-dominant leg in pistol squat was the only significant risk factor (OR = 0.7, p = 0.042). Players that had been injured more severely (> 28 days) before the beginning of the study had significantly higher asymmetry index (AI%) in hop lunge (< 28 days: 25.85%, > 28 days: 52.70%, p = 0.024). Knee angle on non-dominant leg in pistol squat was significantly lower for players that had history of former ankle injury (yes: 70.42°, no: 80.83°, p = 0.033) and other injuries (yes: 67.6° no: 77.1°, p = 0.022). Total index of SLS/OHS was lower for players with history of former other injuries ...